Analysis of FRET Signals in the Presence of Free Donors and Acceptors() - Wlodarczyk, Jakub (The Biophysical Society, 2008)
A method for spectral analysis of Förster resonance energy transfer (FRET) signals is presented, taking into consideration both the contributions of unpaired donor and acceptor fluorophores and the influence of incomplete labeling of the interacting partners. It is shown that spectral analysis of intermolecular FRET cannot yield accurate values of the Förster energy transfer efficiency E, unless one of the interactors is in large excess and perfectly labeled. Instead, analysis of donor quenching yields a product of the form Ef(d)p(a), where f(d) is the fraction of donor-type molecules participating in donor-acceptor complexes and p(a) is the labeling probability of the acceptor. Similarly, analysis of sensitized emission yields a product involving Ef(a). The analysis of intramolecular FRET (e.g., of tandem constructs) yields the product Ep(a). We use our method to determine these values for a tandem construct of cyan fluorescent protein and yellow fluorescent protein and compare them with those obtained by standard acceptor photobleaching and fluorescence lifetime measurements. We call the method lux-FRET, since it relies on linear unmixing of spectral components.